2019
DOI: 10.1177/1069072719876892
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Odds: Gender Differences in Departing the Engineering Profession

Abstract: Women’s departure or nonentrance into science, technology, engineering, and mathematics professions, particularly engineering, has been a lively source of scholarly inquiry for the past three decades. Much of the literature in this area has been with solely female samples of participants, begging the question as to whether or not men and women either choose to leave the profession or not enter for the same or similar reasons. This present study collected a large sample of men ( n = 1,273) who had eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…While women also reported lack of advancement opportunities, loss of interest and dissatisfaction with daily tasks as reasons for leaving engineering positions, the highest reported reason was the lack of time available to spend with their families. That is, in the context of the Theory of Work Adjustment framework, Fouad et al (2020) found that women who left engineering positions felt that their status and comfort needs were not being met. While comfort values include elements of the work environment related to security, compensation, working conditions and level of engaging and varied work, status values reflect the availability of advancement opportunities, recognition, authority and status.…”
Section: Family Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…While women also reported lack of advancement opportunities, loss of interest and dissatisfaction with daily tasks as reasons for leaving engineering positions, the highest reported reason was the lack of time available to spend with their families. That is, in the context of the Theory of Work Adjustment framework, Fouad et al (2020) found that women who left engineering positions felt that their status and comfort needs were not being met. While comfort values include elements of the work environment related to security, compensation, working conditions and level of engaging and varied work, status values reflect the availability of advancement opportunities, recognition, authority and status.…”
Section: Family Formationmentioning
confidence: 99%
“…Among women with undergraduate degrees in engineering, the differences between those who stayed and those who left engineering occupations were due not to differences in self-confidence or changes in interests, but rather to differences in work-related support for work–life roles and in receiving support for advancement (Fouad et al , 2016). Comparing men and women engineers, Fouad et al (2020) showed that the top four reasons that men left engineering positions include lack of advancement opportunities, loss of interest, salary and dissatisfaction with daily tasks. While women also reported lack of advancement opportunities, loss of interest and dissatisfaction with daily tasks as reasons for leaving engineering positions, the highest reported reason was the lack of time available to spend with their families.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note, naturally, that increasing the proportion of women and underrepresented groups into STEM education and professions is very complex and requires far more than career interventions or enhanced STEM education. As many scholars and advocates have noted, structural changes are needed to create equitable opportunities for all students and individuals to succeed and develop their potentials (e.g., Blustein, 2019;Byars-Winston, 2014;Fouad et al, 2019). However, career practitioners and educators can potentially have a major impact on the lives of the students and clients who are exposed to STEM-infused practices and pedagogy.…”
Section: A Critical Analysis Of the Intersection Of Stem Education An...mentioning
confidence: 99%
“…The disproportionately low representation of women and individuals from U.S. racial and ethnic minority groups in engineering education and the engineering workforce is well documented and has been an area of study across multiple disciplines for many years (Fouad et al, 2020; Jacobs, 2005; Lent et al, 2005). Engineering advanced degrees earned by women and other historically underrepresented (HU) 1 individuals have increased since 2010 yet remain far from parity with white males when compared with overall graduate candidates (Women, Minorities and Persons with Disabilities in Engineering, 2021) or when compared the U.S. population demographic makeup (U.S.…”
mentioning
confidence: 99%